Evidence of the differential sensitivity of neogastropods to tributyltin (TBT) pollution, with notes on a species (Columbella rustica) lacking the imposex response - Gibbs, P. E. (2020)
Five neogastropod species collected from a tributyltin (TBT)-polluted site near the port of Fare within the Ria Formosa on the Algarve coast of Portugal were examined in April 1996 for 'imposex'. All females of four of these species - Hexaplex trunculus, Ocenebra erinacea, Ocinebrina aciculata (all Muricidae) and Nassarius reticulatus (Nassariidae) - exhibited the characteristic development of male sex organs (penis plus vas deferens) but no female of the fifth Columbella rustica (Columbellidae) - showed any sign of being similarly masculinised. Only two neogastropods have been previously described as lacking the imposer response to TBT exposure. These two species, along with C. rustica, can be considered as 'zero-response' forms. Other species can be grouped according to the maximum level of masculinisation they exhibit: level I species develop just a penis and vas deferens; in level II forms oviduct structure and function are disrupted, and in level III species ovary transformation to testis is observed. Such a comparative scheme of ordering can be used as a guide to the differential sensitivity of species to TBT pollution.